1998
DOI: 10.1002/pro.5560070111
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal phosphoproteins. Identification of a hexosephosphate mutase and the α‐subunit of succinyl‐CoA synthetase in the extreme acidothermophile Sulfolobus solfataricus

Abstract: When soluble extracts from the extreme acidophilic archaeon Sulfolobus solfataricus were incubated with [Y-'~P]ATP, several radiolabeled polypeptides were observed following SDS-PAGE. The most prominent of these migrated with apparent molecular masses of 14, 18, 35, 42, 46, 50, and 79 kDa. Phosphoamino acid analysis revealed that all of the proteins contained phosphoserine, with the exception of the 35-kDa one, whose protein-phosphate linkage proved labile to strong acid. The observed pattern of phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Phosphorylated proteins have been detected in several halophilic, methanogenic, and thermophilic archaeons (11,26,48,62,63,65,66,68,69), and in several cases the observed patterns of protein phosphorylation exhibited the type of environmentally sensitive changes suggestive of regulatory control (48,62,68,69). A CheA-like two-component cascade responsible for modulating chemo-and phototaxis has been characterized for the halophilic archaeon Halobacterium halobium (52,53), while protein-serine/threonine phosphatases belonging to the PPP family of enzymes first discovered in the Eucarya have been described for the archaeons Sulfolobus solfataricus (32,37), Methanosarcina thermophila TM-1 (49,67), and Pyrodictium abyssi TAG11 (41).…”
mentioning
confidence: 99%
“…Phosphorylated proteins have been detected in several halophilic, methanogenic, and thermophilic archaeons (11,26,48,62,63,65,66,68,69), and in several cases the observed patterns of protein phosphorylation exhibited the type of environmentally sensitive changes suggestive of regulatory control (48,62,68,69). A CheA-like two-component cascade responsible for modulating chemo-and phototaxis has been characterized for the halophilic archaeon Halobacterium halobium (52,53), while protein-serine/threonine phosphatases belonging to the PPP family of enzymes first discovered in the Eucarya have been described for the archaeons Sulfolobus solfataricus (32,37), Methanosarcina thermophila TM-1 (49,67), and Pyrodictium abyssi TAG11 (41).…”
mentioning
confidence: 99%
“…It is clear that archaeal proteins also become phosphorylated on serine, threonine, and tyrosine residues (34,35,37,38,40,41). However, little hard data concerning the enzymes responsible exist (34,35).…”
mentioning
confidence: 99%
“…Among the more visually prominent of these was a polypeptide with an apparent mass of ϳ46-kDa that contained [ 32 P]phosphoserine (41). The large number of polypeptides present in the extract rendered the unambiguous identification of the Coomassie stained band corresponding to the ϳ46-kDa phosphoprotein problematic.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we observed that when extracts of the hyperthermophilic archaeon Sulfolobus solfataricus were incubated with [␥- 32 P]ATP, numerous polypeptides incorporated radiolabeled phosphate (41). One of the more visually prominent of these was a phosphoserine-containing polypeptide with a mass of ϳ46 kDa.…”
mentioning
confidence: 98%